Item Analysis of the Final Semester Evaluation in Madrasah Ibtidaiyah Thotiqul Huda Malang - FAQIH, FAQIH ZAINAL ABIDIN; Maghfiroh; NUR QOMARI (Education Reserach Center, 2025)
This study aims to analyze the quality of the final semester evaluation items for the Arabic language subject of fifth-grade students at Thoriqul Huda Islamic Elementary School (Madrasah Ibtidaiyah) in Wagir. The study employed a quantitative descriptive method with documentation techniques as the data collection tool, which included the test items, answer keys, and student responses. The data were analyzed using